Adductor-related groin pain in team sport athletes: A narrative review and practical considerations for the strength and conditioning coach - Toum, M. (Journal of Australian Strength and Conditioning, 2021)
Strength and Conditioning practitioners should have a key role within the multidisciplinary team in rehabilitating and preventing adductor-related groin pain in team sport athletes, with strategies aimed towards improving hip adductor strength, multiplanar intersegmental control and linear and multidirectional running mechanics.